Telecommunications survival guide - Moulton, Pete 1944- (Prentice Hall, 2001)
Telecommunications Survival Guide will help any professional understand all of today's most important new telecommunications, networking, and high-speed Internet technologies-and how to profit from them! Leading author and consultant Peter Moulton explains today's telecom revolution in straightforward, easy-to-follow language-with plenty of pictures, diagrams, and business examples. From wireless to LANs, DSL to satellite communications, you'll learn how it works, why it matters, and how you can use it to save money and reach new customers.